Learning Rails - St. Laurent, Simon (O'Reilly Media, 2008)
While most books written about Rails cater to programmers looking for information on data structures, Learning Rails targets web developers whose programming experience is tied directly to the Web. Rather than begin with the inner layers of a Rails web application--the models and controllers--this unique book approaches Rails development from the outer layer: the application interface. You'll learn how to create something visible with Rails before reaching the more difficult database models and controller code. With Learning Rails, you can start from the foundations of web design you already know, and then move more deeply into Ruby, objects, and database structures. This book will help you: Present web content by building an application with a basic view and a simple controller, while learning Ruby along the way Build forms and process their results, progressing from the simple to the more complex Connect forms to models by setting up a database, and use Rails' ActiveRecord to create code that maps to database structures Use Rails scaffolding to build applications from a view-centric perspective Add common web application elements such as sessions, cookies, and authentication Build applications that combine data from multiple tables Create simple but dynamic interfaces with Rails and Ajax Once you complete Learning Rails, you'll be comfortable working with the Rails web framework, and you'll be well on your way to becoming a Rails guru.